Role of Notary in Registration of Fidusian Warranties to Obtain Fidusian Warranty Certificate - Haryanto Haryanto (Sultan Agung Notary Law Review, 2021)
In this modern era and the development of technology that continues to develop significantly encourages many parties to make better use of technology wisely & well, and maximally, this is also utilized by the government. In providing public services including the Directorate General of General Legal Administration (Ditjen AHU) Ministry of Law and Human Rights of the Republic of Indonesia. Launched the Online Fiduciary Guarantee Certificate registration program. Which is where the role of the Notary in this case plays a very important role before the issuance of the online program Creditor or Fiduciary Security Recipient or Proxy to obtain a Fiduciary Guarantee Certificate must register conventionally or manually where the applicant must come to the office of the Directorate General of General Legal Administration (Ditjen AHU) of the Ministry Law and Human Rights of the Republic of Indonesia in their respective provinces, which of course require a lot of time and money. So with the implementation of the Fiduciary Guarantee Certificate registration program online. Of course, you get a lot of benefits both in terms of economics and efficiency, of course, more practical and faster. So with the implementation of the Fiduciary Guarantee Certificate registration program online. Of course, you get a lot of benefits both in terms of economics and efficiency, of course, more practical and faster. So with the implementation of the Fiduciary Guarantee Certificate registration program online. Of course, you get a lot of benefits both in terms of economics and efficiency, of course, more practical and faster. formulation of the problem of how the Notary's Role in Fiduciary Security Certificate Registration to Obtain a Fiduciary Guarantee Certificate, as well as Obstacles and Solutions in Implementing Online Fiduciary Guarantee Certificate Registration at the Directorate General of General Law Administration (Ditjen AHU), Ministry of Law and Human Rights of the Republic of Indonesia With the enactment of Online Fiduciary Registration at the Directorate General of General Legal Administration (Ditjen AHU), Ministry of Law and Human Rights of the Republic of Indonesia is very beneficial for the general public, especially Debtors, Creditors, Notaries and the Government itself as well as financing institutions. Although there are still good obstacles in the nature of the regulatory substance of Act No. 42 of 1999 concerning Fiduciary Security, there is a lack of discipline in law and culture in society. Because if the rule of law, lack of legal discipline, and community culture are not improved, then justice, legal certainty, and benefits will not be felt by the community itself. It is hoped that in the future it will be better and require commitment from the general public, especially those related to the Fiduciary Guarantee.